Refolding of SDS-Unfolded Proteins by Nonionic Surfactants - Kaspersen, Jørn Døvling (Biophys J, 2017)
The strong and usually denaturing interaction between anionic surfactants (AS) and proteins/enzymes has both benefits and drawbacks: for example, it is put to good use in electrophoretic mass determinations but limits enzyme efficiency in detergent formulations. Therefore, studies of the interactions between proteins and AS as well as nonionic surfactants (NIS) are of both basic and applied relevance. The AS sodium dodecyl sulfate (SDS) denatures and unfolds globular proteins under most conditions. In contrast, NIS such as octaethylene glycol monododecyl ether (C(12)E(8)) and dodecyl maltoside (DDM) protect bovine serum albumin (BSA) from unfolding in SDS. Membrane proteins denatured in SDS can also be refolded by addition of NIS. Here, we investigate whether globular proteins unfolded by SDS can be refolded upon addition of C(12)E(8) and DDM. Four proteins, BSA, α-lactalbumin (αLA), lysozyme, and β-lactoglobulin (βLG), were studied by small-angle x-ray scattering and both near- and far-UV circular dichroism. All proteins and their complexes with SDS were attempted to be refolded by the addition of C(12)E(8), while DDM was additionally added to SDS-denatured αLA and βLG. Except for αLA, the proteins did not interact with NIS alone. For all proteins, the addition of NIS to the protein-SDS samples resulted in extraction of the SDS from the protein-SDS complexes and refolding of βLG, BSA, and lysozyme, while αLA changed to its NIS-bound state instead of the native state. We conclude that NIS competes with globular proteins for association with SDS, making it possible to release and refold SDS-denatured proteins by adding sufficient amounts of NIS, unless the protein also interacts with NIS alone.